Museum : Revista mensual de Arte español antiguo y moderno y de la vida artística contemporánea. (Barcelona : Establecimiento Gráfico Thomas, 1911)
Monthly art journal, illustrated with photographs. It presents research on painting, sculpture, architecture, archeology, ceramics, glassware, coins, jewelry, woodcuts, tapestries, embroideries, interior decoration, etc. (uit: https://ddd.uab.cat/record/60290?ln=en)
Online UAB (Universitat Autònoma de Barcelona): https://ddd.uab.cat/record/60290
Spaans
Tijdschriften